Studi Eksperimental Pengaruh Variasi Sudut Kemiringan terhadap Temperatur Onset Termoakustik Generator Gelombang Berdiri dengan Panjang Resonator 780 mm - Rinasa Agistya Anugrah (Proklamasi 45 University, 2018)
Onset temperature is one of the most important parameters in thermoacoustic generator to be researched. In that application, onset temperature can representated how many the performance of this device, if seen by input energy, used the system of the thermoacoustic generator. Decreasing onset temperature so decreases the energy that used to generate acoustic energy in thermoacoustic generator. In this researched would be done research of variation of tilted angles -90º, 0º, dan 90º with constant 780 mm of resonator length. The method used two thermocouples installed between the stack side to measure temperature of HHX and CHX, and the ΔT called onset temperature. It would be found the effective tilted angle that used, so the performance is on the best value represented by the least onset temperature. The result is when the tilted angle decrease so the onset temperature became decreased too. In this research, if seen by the input energy, the best performance of thermoacoustic generator is on -90º of tilted angle.